Essential logic for computer science - Page, Rex L.; Gamboa, Ruben (The MIT Press, 2018)
Subject: Applications of logic in computer science Contents: predicate logic, proofs, equation-based software and digital circuits, automated testing and theorem provers, large-scale computation Intent: undergrad CS majors will learn how to apply predicate logic to testing and verification of software and digital circuits Unique treatment: lower division courses focus on applications in computer science (just enough theory for applications) widely-used, automated theorem prover (ACL2) supports logic applications descriptive coverage of large-scale computation Computer science undergrads use logic for testing and verification of software and digital circuits.--Provided by publisher.